The relationship between neck pain and hand dexterity among violinists in Kota Kinabalu, Sabah, Malaysia - Le, Tay Xin; Vasanthi, Rajkumar Krishnan; Brown, Clement Jim (Diva Enterprises Pvt Ltd, 2019)
Background and Objective